2020
DOI: 10.1097/md.0000000000023115
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of the 100 most influential papers on peritoneal dialysis

Abstract: Background: We aimed to identify the 100 most cited articles published on peritoneal dialysis (PD) and analyze their characteristics to provide information on the achievements and developments of PD research over the past decades. Methods: The Science Citation Index Expanded (SCIE) in the Web of Science Core Collection was comprehensively searched from 2000 to 2018, using the keywords “Peritoneal dialysis” or “Dialyses, Peritoneal” or “Dialysis, Periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The United States (37.15), China (34.63), and Japan (28.09) had the highest hT-index in HD/PD articles, indicating that the hT-index taking into account all publications and citations can be utilized in academics and practices, especially when used in conjunction with radar diagrams to compare authors and institutes at a glance. The results are consistent with the findings in previous studies: authors from the United States were present in 30.6% of 7618 PD papers in 887 journals (6991 articles and 627 reviews), [31] and the United States was the most productive country (n = 51) of the 100 most influential papers on peritoneal dialysis, [32] IRAs dominated by the United States had been verified. The Collatz data are in the upper triangle; the HD/PD data in the lower triangle; the h T -index is more similar to the h-index.…”
Section: Additional Informationsupporting
confidence: 92%
See 2 more Smart Citations
“…The United States (37.15), China (34.63), and Japan (28.09) had the highest hT-index in HD/PD articles, indicating that the hT-index taking into account all publications and citations can be utilized in academics and practices, especially when used in conjunction with radar diagrams to compare authors and institutes at a glance. The results are consistent with the findings in previous studies: authors from the United States were present in 30.6% of 7618 PD papers in 887 journals (6991 articles and 627 reviews), [31] and the United States was the most productive country (n = 51) of the 100 most influential papers on peritoneal dialysis, [32] IRAs dominated by the United States had been verified. The Collatz data are in the upper triangle; the HD/PD data in the lower triangle; the h T -index is more similar to the h-index.…”
Section: Additional Informationsupporting
confidence: 92%
“…The articles published by the 2 prolific authors were doted on the dashboard-type IBP, as shown in Figure 7 , [ 50 ] in lieu of the 100 articles on PD listed in a bibliometric study. [ 32 ] Using the IBP is unique and modern and never seen before in the literature. The impact IBP displays the author document profile in a single view and shows more context than a single metric, such as a citation metric (or the h-index), which provides us with bibliometrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-six percent of the 7618 papers on peritoneal dialysis published in 887 journals were written by American authors (6991 articles and 627 reviews), [ 68 ] and the United States was the most productive country (n = 51) among the top 100 influential papers on peritoneal dialysis. [ 69 ] In HD/PD articles, the United States had the highest hT index (=37.15) compared to many other countries. These results are consistent with our findings regarding the dominance of the United States in articles regarding CHPR-related UTI since 2013 (hT-JIF = 38.30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many articles include many tables and graphs in bibliometrics without utilizing radar plots and chord diagrams to condense information that is of interest to readers, as we did in Figures 1 and 2, especially using the dot plot in Figure 5 to display all those T100NurseR articles on a dashboard and save space compared to those with 100 and 50 articles listed in their studies [67,68] or 42 tables and graphs in an article. [69] To visualize dynamics related to contraceptive use and to apply data, chord diagrams [36,[38][39][40] were used.…”
Section: Chord Diagrams Used To Present the Relationship Between Them...mentioning
confidence: 99%